Maternal mortality report (London : The Maternal Mortality Committee)
1934-10 1934 1930s 19 pages special consideration in areas in which illegal abortion is believed to be of frequent occurrence. In order to ascertain as far as possible the extent to which Local Authorities are using their powers under the Maternity and Child Welfare Act, the reports of Medical Officers of Health have again been analysed. We desire to express our appreciation of the kindness of Medical Officers in supplying copies of their reports, and, in some cases, in giving supplementary information. COUNTY COUNCILS There are sixty-two administrative counties in England and Wales. Of these we have analysed sixty-one reports for the year 1932. As far as we can gather from the reports of the Medical Officers of Health of the County Councils, the position with regard to the powers of a Local Authority under the Maternity and Child Welfare Act, 1918, is as follows :— (1) The appointment of Health Visitors, whose duties include Attendance at an Ante-natal and Post-natal Centre, and the visiting of expectant mothers. All have Health Visitors, part of whose duty is to visit the expectant mothers. It will be observed later that there are County Councils who apparently have no ante-natal centres, and it is difficult to see what, if any, arrangement is made for post-natal examination. (2) The establishment of Ante-natal Clinics for expectant mothers, and of Post-natal Clinics which mothers can attend immediately after confinement. In forty counties it is stated that ante-natal clinics have been established. (3) Assistance to Midwives. (a) Provision of sterilised maternity outfits free or at cost price. This very valuable provision is carried out by sixteen County Councils. These figures do not include "bags" lent. (b) A subsidy to enable a midwife to practise in a district which would otherwise not support her. This power is used by nineteen. (c) The appointment, where necessary, of municipal midwives. This power is used by two. We have only included midwives employed by municipal hospitals or nursing homes where these are specifically stated to be working on a district. (d) The payment of part fees to a midwife when the patient cannot afford the full fee. (4) 292/824/1/20